The Effect of Neighborhood Disadvantage and Parental Involvement on African American Adolescent’s Externalizing Behavior and Academic Outcome - Lopez Tamayo, Roberto G (2015)
African American adolescents are more likely to live in disadvantaged neighborhoods than their European American counterparts. The impact that neighborhood disadvantage such as poverty, unemployment, population turnover, and community violence exerts on youth’s behavior becomes more prevalent as they grow older, increasing the risk for engaging in externalized behavior and hindering academic outcomes. Consistent with the developmental theory, an examination of parental involvement (PI) as moderator between neighborhood disadvantage and externalizing behavior is warranted. There is a dearth of longitudinal research that examines how neighborhood disadvantage operates and, to what extent influences, directly or indirectly, behaviors and academic outcomes of African American high school students. A sample of 519 students, 9th to 11th grade (45% females) with a mean age of 14.8 years (SD± 0.35), participated in the present study. Nearly half of the participants (45.6%) were eligible for free or reduced lunch. A moderated mediation model was proposed in which externalizing behavior mediates the association between neighborhood disadvantage and academic outcomes, and parental involvement moderates the association between neighborhood disadvantage and externalizing behavior. Path analysis employing maximum likelihood was conducted using Mplus7 to examine the associations between study variables. Results from the moderated mediation analysis supported that parental involvement (PI) served as a protective factor against neighborhood disadvantage exposure. Specifically, in the low (PI) group, poverty and community violence in 9th grade predicted externalizing behavior in 10th grade, whereas in the high PI group, unemployment in 9th grade predicted externalizing behavior in 10th grade. With regard to academic outcomes, in the low PI group, population turnover in 9th grade predicted low academic outcomes in 11th grade. In contrast, in the high PI group, none of the neighborhood disadvantage variables was related to academic outcomes in 11th grade was which in turn predicted negative academic outcomes in 11th grade. The only significant path that remained significant in both, low and high PI groups, was the strong association between externalizing behavior in 10th grade and academic outcomes in 11th grade. Mediation analysis using Bootstrapped standard errors procedure indicated indirect effects from poverty to academic outcome via externalizing behavior, and community violence to academic outcome via externalizing behavior in the low PI group, whereas there was no significant indirect effects in the high PI group. These results are a robust support for moderated mediation effects. The use of a defined epidemiological sample facilitates generalization of findings to individuals from the same ethnic group living in similar neighborhoods. Preventive interventions need to capitalize on specific characteristics of the African American community, such as strong family ties and collectivism to enhance the social fabric. Promotion of social capital through increased collaboration between families, community agencies and institutions may provide more resources for youth to achieve academic outcomes